Development of bismuth borosilicate glass doped with Eu3+ for reddish orange emission materials application. (2017) - Rakpanich, S.; Wantana, N.; Kaewkhao, J.
Abstract: Eu 3+ doped bismuth borosilicate (BiBSi:Eu 3+ ) glasses were prepared by melt quenching technique, in the chemical composition of 40Bi2 O3 :(40-x)B2 O3 :20SiO2 :xEu2 O3 by varying Eu2 O3 concentration from 0.0 to 5.0 mol%. The results show that Eu 3+ doping in higher concentration make the glass molar volume tend to increase. This cause by increasing of non-bridging oxygen (NBOs) in glass network. The absorption spectra indicate photon absorbing of Eu 3+ in visible light and near infrared region. From emission spectra, Eu 3+ doped glasses perform the strongest emission at 613 nm ( 5 D0 → 7 F2 ) wavelength by 465 nm excitation. The optimum concentration of Eu 3+ with strongest emission in bismuth borosilicate glass is 4.0 mol%. The CIE 1931 chromaticity investigation show that Eu 3+ doped glass emitted the light with reddish orange color.